ASSESSMENT OF POLLUTION LOAD INTO TAM GIANG - CAU HAI LAGOON AND A PREDICTION TO 2020 - Trang, Cao Thi Thu; Thanh, Tran Duc; Sinh, Le Xuan (Vietnam Journal of Marine Science and Technology, 2014)
Based on the statistic data of social-economic present and development planning to 2020 of Thua Thien Hue province, land-base pollution load from development activities has been calculated by using the rapid assessment of the marine coastal environment method. The calculating results shown that, each year, development activities in Thua Thien Hue province create about 128 thousand tons of COD, 73 thousand tons of BOD, 25 thousand tons of Nitrogen, 10 thousand tons of Phosphorous and 875 thousand tons of TSS from living activities, aquaculture, industry, farming and land washing. Until 2020, this amount of waste will be increased 1.3 - 1.4 times, even double compare to present. There is 50% to 60% of the waste discharged into the Tam Giang - Cau Hai lagoon. The main pollution sources are from domestic ones included residents and tourists, and livestock farms. Therefore, treatment of waste from those sources is very necessary to minimize the amount of waste into the lagoon.